2017
DOI: 10.30977/at.2219-8342.2017.40.0.75
|View full text |Cite
|
Sign up to set email alerts
|

Induction Heating in History and Development. Application in Modern Transport Repairing Technologies

Abstract: The technologies used in repair of vehicles were analyzed in the given paper. The shortcomings of the mechanical repair methods in question can be solved by using induction heating. Analysis of the stages of development and implementation of induction heating in industries showed effective performance of this technology and its opportunities for further improvement. An alternative repair technique, which consists in using induction heating, was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Studies have shown that ~ 86.4% of the total amount of Lenz-Joule heat is released in the skin layer. In addition, the size of the skin layer, and accordingly the heating, also depends on the relative magnetic permeability of the metal of the processed object [22,23].…”
Section: Induction Heatingmentioning
confidence: 99%
“…Studies have shown that ~ 86.4% of the total amount of Lenz-Joule heat is released in the skin layer. In addition, the size of the skin layer, and accordingly the heating, also depends on the relative magnetic permeability of the metal of the processed object [22,23].…”
Section: Induction Heatingmentioning
confidence: 99%
“…дослідження, у скін-шарі виділяється ~ 86,4 % від загальної кількості Ленц-Джоулевої теплоти. Крім того, величина скін-шару, а відповідно і нагрівання, також залежить від відносної магнітної проникності металу об'єкта, що обробляється[14,15].…”
unclassified